Toxcity of cowdung cake smoke to storage insects - SRIVASTAVA, CHITRA; SINHA, S N; REDDY, D SRINIVASA (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2004 on the effect of cowdung cake smoke on adult and egg stages of storage insects. More than 80% ,martality of pulse beetle, Callosobruchus maculatus (Fabricius) was observed with 24 hr exposure of cow dung cake smoke. The LD value of phosphine for susceptible (0.104 mg/l) and field strain (0.413 mg/litre) of Rhizopertha dominica (Fabricius) was reduced to nearly half being O.052mg/litre and O.264mg/litre respectively treated with smoke prior to bioassay with phosphine. Hatchability of eggs of different storage insects was reduced with smoke treatment. One-day-old eggs showed maximum susceptibility to smoke (data %).